A quality improvement initiative to increase HIV post-exposure prophylaxis treatment for emergency department patients after sexual assault: A pre-post study - Douglas A.E. White; Montana Jewett; Molly Burns; Cedric Rodriguez; Cinthya Mujica Pinto; Gabriela Regalado; Kevin Del Angel; Hillary J. Larkin; Erik S. Anderson (PLoS ONE, 2025)
Background Many emergency department (ED) patients after a sexual assault face barriers to receiving HIV post-exposure prophylaxis (PEP). We implemented a quality improvement initiative which updated the sexual assault electronic health record (EHR) template and made available free, full-course PEP treatment packs for use at provider discretion. The aim of this study was to compare the receipt of HIV PEP for ED patients receiving sexual assault care before and after the initiative. Methods This was a retrospective, quasi-experimental, pre-post study of all ED patients who completed a sexual assault examination between June 1, 2022 – January 31, 2023 (pre-intervention) and March 1, 2023 – October 31, 2023 (post-intervention). An odds ratio (OR) and 95% confidence interval (CI) were calculated to determine the initiative’s effect on PEP prescribing. Multivariable logistic regression models estimated the independent effect of the initiative while controlling for potential confounders. Results Of the 235 sexual assault examinations, 117 (49.8%) were during the pre-intervention and 118 (50.2%) were during the post-intervention periods. Pre-intervention, the mean age was 33.0 years (standard deviation [SD] 12.3), 94.0% were female, 30.8% Black, 31.6% Latinx, and 28.2% White. Post-intervention, the mean age was 29.2 years (SD 12.6), 90.7% were female, 42.4% Black, 28.8% Latinx, and 17.8% White. Patients were more likely to receive HIV PEP post-intervention (33/118, 28.0%) than pre-intervention (11/117, 9.4%) (OR 3.7, 95% CI 1.8 to 7.8). The independent effect of the initiative on HIV PEP prescribing remained significant after controlling for demographics (OR 3.6, 95% CI 1.6 to 8.0), assault characteristics (OR 4.2, 95% CI 1.6 to 11.1), and provider experience (OR 3.5, 95% CI 1.7 to 7.5). Conclusion The availability of HIV PEP treatment packs plus a modification to the EHR template led to a significant increase in the provision of HIV PEP for ED patients after sexual assault.